2023
DOI: 10.1021/acsnano.3c01792
|View full text |Cite
|
Sign up to set email alerts
|

A Paclitaxel Prodrug with Copper Depletion for Combined Therapy toward Triple-Negative Breast Cancer

Abstract: Tuning the content of copper is of great significance for the treatment of cancer and neurodegenerative diseases. Herein, we synthesized a redox-responsive paclitaxel (PTX) prodrug by conjugating PTX with a copper chelator through a disulfide bond. The as-fabricated prodrug (PSPA) showed specific chelation toward copper ions and could assemble with distearoyl phosphoethanolamine-PEG 2000 to form stable nanoparticles (PSPA NPs) in aqueous media. Upon being internalized by tumor cells, PSPA NPs could respond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Their findings provide guidance for the design and optimization of future mRNA cancer vaccines. The chemotherapeutic drug docetaxel is commonly used in the treatment of many human malignancies, including nonsmall cell lung cancer, breast cancer, ovarian cancer, and hormone-refractory prostate cancer. In one study, Fotin-Mleczek et al combined docetaxel with the two-component mRNA vaccines which could encode OVA and induce self-adjuvant action via TLR-7 pathway, leading to a significant delay of tumor growth and more effective antitumor capacity, whether compared to OVA mRNA vaccination or chemotherapeutic drugs alone . Similar results were also observed when they combined cisplatin with two-component mRNA vaccines.…”
Section: Strategies To Enhance the Efficacy Of Mrna Cancer Vaccinesmentioning
confidence: 78%
“…Their findings provide guidance for the design and optimization of future mRNA cancer vaccines. The chemotherapeutic drug docetaxel is commonly used in the treatment of many human malignancies, including nonsmall cell lung cancer, breast cancer, ovarian cancer, and hormone-refractory prostate cancer. In one study, Fotin-Mleczek et al combined docetaxel with the two-component mRNA vaccines which could encode OVA and induce self-adjuvant action via TLR-7 pathway, leading to a significant delay of tumor growth and more effective antitumor capacity, whether compared to OVA mRNA vaccination or chemotherapeutic drugs alone . Similar results were also observed when they combined cisplatin with two-component mRNA vaccines.…”
Section: Strategies To Enhance the Efficacy Of Mrna Cancer Vaccinesmentioning
confidence: 78%
“…In previous research works, it has been observed that bioavailable copper contributes to tumor growth, proliferation, angiogenesis, and metastases. Various research studies depicted that copper depletion induces metastasis, and copper detection might be a promising approach to enhance significant survival benefits in high-risk triple-negative breast cancer (TNBC) patients . A recent work demonstrated that copper depletion induces significant oxidative stress and abnormal-metabolism-mediated cell death, which opens up copper depletion therapy to be an effective diagnostic platform against triple-negative breast cancer . However, the concentration of copper in TNBC patients remains significantly higher compared to other metals, so in this study, we evaluated Cu­(II) detection using the photoswitchable polymer in MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org Hao et al, 2022;Hao et al, 2023;Lu et al, 2023). The reduction-responsive nanoparticles exhibited excellent promise in improving bioavailability, realizing the efficient use of drugs (An et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…Rationally designed controlled nanoparticles are imperative to guarantee a good therapeutic window. Tumor microenvironment overexpressed biomarkers, including acid, hypoxia, and redox, provide munch chance to build responsive nanosystems to enhance the tumor-specific cell-killing efficacy ( Li et al, 2021 ; Lu et al, 2021 ; Xia et al, 2021 ; Hao et al, 2022 ; Hao et al, 2023 ; Lu et al, 2023 ). The reduction-responsive nanoparticles exhibited excellent promise in improving bioavailability, realizing the efficient use of drugs ( An et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%